Healthcare Workers’ Compliance with Hand Hygiene After the Introduction of an Alcohol-Based Handrub - Chittaro, Michele; Calligaris, Laura; Farneti, Federico; Faruzzo, Alda; Panariti, Mateo; Brusaferro, Silvio (International Journal of Infection Control, 2009)
Hand hygiene of Health Care Workers (HCWs) is a basic measure of hospital infection control but compliance is extremely low. The present study, carried out in intensive care, surgical and medical area of an University Hospital, evaluates the effects of the introduction of an alcohol based handrub among HCWs. It consisted in three surveys: before and at 7 and 30 days after the product introduction. Overall 432 nurses’ working-hours and 3451 handwashing occasions were observed. The compliance increased significantly from 19.3% (244/1262) in survey 1, to 28.1% (314/1119) and 27.1% (288/1070) (p<0.01) in survey 2 and 3 respectively. Compliance was more frequent after performing 39.1% (443/1133) a nursing procedure than before it 15.7% (329/2092) (p<0.01). Furthermore, compliance significantly decreased with the increase in number of hand hygiene occasions per nurse working hour only when the handrubbing had not been introduced yet [30.2% 0-7 occasions/h vs 21.8% >8 occasions/h (p<0.05)]. Gender did not affect compliance. Results are consistent with other studies published in literature that remark the problem of limited adherence to the handwashing guidelines. In fact, the compliance in the three surveys was <30%. The higher compliance observed after the execution of nursing procedures shows that the staff is more concerned with its own safety than the patient’s. Keywords: handwashing, handrub, compliance, hospital, healthcareworker.